Local Treatment of Hand-Foot Syndrome with Uridine/Thymidine: In Vitro Appraisal on a Human Keratinocyte Cell Line HaCaT - J. Hartinger; P. Veselý; E. Matoušková; S. Argalacsová; L. Petruželka; I. Netíková (The Scientific World Journal)
5-fluorouracil (5-FU) is one of the most commonly used antineoplastic drugs in the anticancer therapy. The hand-foot (HF) syndrome (palmar-plantar erythrodysesthesia) is an adverse effect frequently related to long-term i.v. administration of 5-FU or its orally applicable prodrug capecitabine. Its severity can even lead to interruption of the otherwise effective anticancer therapy. Tentative practice in some clinics has shown that topical application of 10% uridine ointment is beneficial for calming down the HF syndrome. This study is focused on verifying the alleged protective activity of uridine in the in vitro model of cultured human keratinocyte cell line HaCaT. We also tested the protective effects of thymidine alone or uridine-thymidine combination. The cellular viability time progression was measured in order to evaluate the effect of protective agents by three different types of cytopathogenicity tests—NTCA test (non-destructive test of cellular activity), modified MTT test and RTCA (real-time cell analyser, Roche). All three methods proved the ability of uridine and uridine-thymidine combination to protect keratinocytes against 5-FU damage in vitro. While thymidine alone did not show any remarkable effect, the thymidine-uridine combination demonstrated enhanced protective activity compared to uridine alone. Our findings provided the supporting rationale for using uridine or uridine-thymidine ointments in the HF syndrome local therapy.